Current status and influencing factors of social participation in patients undergoing maintenance haemodialysis: a Cross-sectional study following the international classification of functioning, disability, and health framework - W. W. Ge; H. L. Zhang; P. Liu; L. X. Yin (BMC Nephrology)
Abstract Background Maintenance haemodialysis (MHD) has emerged as a primary treatment modality in individuals with end-stage kidney disease. However, haemodialysis not only affects physiological well-being but also significantly influences patients’ social engagement and quality of life. Consequently, investigating the present status and repercussions on social participation among individuals undergoing MHD has evolved as a crucial area of research. This study aimed to investigate the current status of social participation among patients undergoing MHD and analyse the influencing factors, providing a theoretical basis for clinical intervention. Methods This cross-sectional study utilised a convenience sampling method to select 441 patients undergoing maintenance haemodialysis (MHD) at seven tertiary hospitals in Lianyungang between January and May 2024 as survey participants. The study employed a general information questionnaire along with several assessment tools, including the Chinese version of the Impact on Participation and Autonomy; Social Support Rating Scale; Hospital Anxiety and Depression Scale; Pittsburgh Sleep Quality Index; Chinese version of the Functional Assessment of Chronic Illness Therapy-Fatigue; and Medical Outcomes Study Health Status Short Form. Patients with end-stage renal disease aged ≥ 18 years and undergoing MHD for ≥ 3 months were included. Those with other severe illnesses, psychiatric disorders, personality disorders, or inability to cooperate with the study were excluded. Multivariate linear regression analysis was used to identify factors influencing social participation in MHD patients. Results The total score of social participation among patients on MHD was 54. Multiple linear regression analysis indicated that, based on the International Classification of Functioning, Disability, and Health framework, total scores of depression, total scores of social support, age, total scores of the fatigue scale, smoking history, and employment status were the main influencing factors of social participation in patients on MHD (P < 0.05). Conclusions The level of social participation among patients on MHD was moderate and in need of enhancement. Healthcare providers should prioritise older, unemployed patients and improve their social participation and quality of life by addressing issues such as fatigue, depression, and enhancing social support.